Determinants of cessation of exclusive breastfeeding in the early postnatal period in Indonesia - Wawan Gunawan; Ratu Ayu Dewi Sartika; Fadila Wirawan; Primasti Nuryandari Putri (AcTion: Aceh Nutrition Journal, 2024)
Breast milk is the main source of nutrients in infants under six months of age. The causes of low exclusive breastfeeding coverage vary from region to region. Lack of husband’s support is one of the factors contributing to exclusive breastfeeding failure. This study aimed to determine the determinants of exclusive breastfeeding failure, designed as a cross-sectional study, conducted in Sawangan District, Depok City, in February 2023. Subjects were selected using the total sampling method, namely all mothers who had babies aged 0-6 months who conducted antenatal checks at Health Center and private midwife clinics who were available to be interviewed and filled out a questionnaire with as many as 224 people and analyzed using the Chi-square test at 95% CI. Results: During antenatal care, the father's role in buying formula/instant porridge/bananas (p= 0,0000 and applying honey or mashed dates to the newborn (p= 0,000) was associated with failure of exclusive breastfeeding in the early postnatal period. Both variables were associated with a 3,7 times higher risk of discontinuing exclusive breastfeeding in the early postnatal period. In conclusion, the determinants of exclusive breastfeeding failure in the early postnatal period were fathers who bought formula/instant porridge/bananas and applied honey or mashed dates to newborns. Socialization and education of fathers regarding the importance of fathers’ involvement in exclusive breastfeeding for mothers is needed.